Phantom development for In-Vitro measurements of MICS band telemetry antenna. (March 2020) - Sulaiman, N H; Samsuri, N A; Rahim, M K A; Inam, M; Seman, F C; Othman, N
Abstract: The paper presents the development of a liquid phantom and In-Vitro testing of Compact Meander Line Telemetry Antenna (CMLTA) by using the developed phantom at 402.5 MHz. A liquid phantom for 402.5 MHz has been developed, and the dielectric properties of the developed liquid phantom have been characterized for verification by using an open-ended probe method. Various composite samples of the solution are developed to characterize material properties for comparison with the theoretical properties at 402.5 MHz (εr = 58.2, σ = 0.82). The comparison between simulated and theoretical permittivity as well as tangent loss is presented. The measured dielectric properties are verified by using open-ended coaxial dielectric kit. Simulated and measured results can be observed in terms of frequency and return loss performance with a deviation of 0.004 MHz and 2.7 dB, respectively.